The impact of quality of work life on organizational commitment - a study of Small and Medium Enterprise in Buon Ma Thuot city - Lê Việt Anh,; Hà Thị Kim Duyên,; Trương Văn Thảo, (Tay Nguyen Journal of Sciences, 2025)
This study examines the impact of Quality of Work Life (QWL) on Organizational Commitment (OCO) among employees in small and medium-sized enterprises (SMEs) located in Buon Ma Thuot City, Vietnam. Drawing on social identity theory, the research analyzes various dimensions of QWL— including job security, rewards, career development, work environment, and social integration—and how they influence employees’ commitment to the organization. Survey data from 460 employees were collected and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the research hypotheses. The findings confirm that QWL has a significantly positive effect on OCO, with job security and rewards emerging as the most influential factors. Furthermore, the study finds that gender moderates this relationship, with male employees responding more positively than female employees to improvements in QWL. The results highlight the importance of HR policies that enhance job stability, ensure fair compensation, and foster employee engagement, thereby increasing organizational commitment. These findings offer practical suggestions for SMEs to improve employee retention and enhance work performance.